Small procoagulant platelets in diabetes type 2 - Edvardsson, Maria; Oweling, Magnus; Järemo, Petter (Thrombosis research, 2020)
Strong agonist provocation in vitro creates small procoagulant platelets characterized by down-regulated fibrinogen receptors as judged from surface αIIbβ3 activation specific antibody (PAC-1). They further show increased surface Annexin V (binds to platelet membrane phosphatidylserine), lysosomal-associated membrane protein 1 (LAMP-1) (indicates lysosomal release) and exhibit disturbed mitochondria integrity as estimated from mitochondrial transmembrane potential changes. We postulated that some circulating platelets activate continuously thereby forming procoagulant populations in vivo. This study aimed to identify such platelets in diabetes type 2 a condition predisposing for thrombotic events. A linear Percoll™ gradient covering the density span 1.090 to 1.040 kg/L was used to separate whole blood platelets from type 2 diabetic subjects (n = 12) into 17 density subpopulations. The gradient contained theophylline, prostaglandin E1 and EDTA to prevent platelet activation in vitro. A multi-colour flow cytometer was employed for analysing the characteristics mentioned above for all density separated small-sized platelet subfractions. Small platelets were enriched in medium-dense subfractions (nos. 10–13) (1.065–1.053 kg/L). Their PAC-1 activities were significant lower (p < 0.001) as compared to other small-sized subpopulations. They further exposed enhanced surface Annexin V and LAMP-1 together with lower mitochondrial transmembrane potentials. In diabetes type 2 such small circulating platelets showed procoagulant features. •Circulating small semi-dense platelets feature type 2 diabetes.•They display lower surface PAC-1 together with higher Annexin V and LAMP-1.•Such small platelets have procoagulant properties.•The clinical importance for diabetes type 2 must be elucidated.